2013
DOI: 10.1016/j.ijsu.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythropoietin on liver regeneration in an experimental model of partial hepatectomy

Abstract: Our study showed that systemically administering high-dose EPO increases regeneration by affecting the biochemical, morphological, and histopathological parameters after liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…There are various studies about the method and EPO dosage for use in animals, with some suggesting 3.000 UI of EPO/kg subcutaneously [1], 4.000 (UI of EPO/kg intraperitoneal [10]. This study showed that a dose of 200 UI EPO/kg subcutaneously, in spite of being considered a low dose, significantly reduced the regenerative ability of the remaining tissue after liver resection.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…There are various studies about the method and EPO dosage for use in animals, with some suggesting 3.000 UI of EPO/kg subcutaneously [1], 4.000 (UI of EPO/kg intraperitoneal [10]. This study showed that a dose of 200 UI EPO/kg subcutaneously, in spite of being considered a low dose, significantly reduced the regenerative ability of the remaining tissue after liver resection.…”
Section: Discussionmentioning
confidence: 81%
“…One of the distinctive and unique characteristics of the liver is its regenerative ability [1]. Partial hepatic resection is many times the only option for patients suffering with hepatocellular carcinoma and is a procedure frequently used in living-donor liver transplants.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the effect of EPO on hepatic tissue after renal I/R injury was not investigated before. However, the direct effect of EPO on hepatic tissue regeneration was previously investigated and showed that, systemic administration of highdose EPO increases hepatic tissue regeneration after liver resection and improved liver function and histopathology [20] . In addition, a reduction of hepatic apoptosis and necrosis was reported in EPO-treated graft livers [21,22] which might indicate a possible role for EPO in protection of the liver following renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Gul and his team [20] demonstrated that, systemic administration of high-dose erythropoietin promotes regeneration of hepatic tissue by affecting biochemical and histopathological parameters after liver resection. Moreover, Schmeding et al, [21] reported an increase of regenerative capacity in EPO treated rats after major hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…EPO is a glycoprotein that promotes the proliferation and differentiation of erythrocyte precursors. It was reported that high-dose EPO increases liver regeneration by affecting the biochemical, morphological, and histopathological parameters after liver resection [58]. EPO increases brown fat gene expression [59].…”
Section: Liver Group Consists Of Epo Renin Sod Akr and Gshmentioning
confidence: 99%